1998
DOI: 10.1038/sj.bjp.0701972
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic‐pharmacodynamic modelling of the EEG effect of alfentanil in rats: assessment of rapid functional adaptation

Abstract: 1 The purpose of the present investigation was to quantify rapid functional adaptation in the concentration-pharmacological eect relationship of alfentanil in rats using quantitative EEG parameters as a pharmacodynamic endpoint. Three groups of 6 ± 7 rats received in a randomized fashion two consecutive infusions of 2.00, 3.14, or 4.24 mg/kg 71 of alfentanil in 20, 40 or 60 min, respectively. The EEG was continuously recorded and frequent arterial blood samples were collected for determination of the alfentani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 42 publications
(49 reference statements)
1
7
0
Order By: Relevance
“…An infusion of ketamine was administered at a constant rate of 10 mg kg ±1 min ±1 over 5 min; serial arterial blood samples were taken before, then at 1. 5,3,5,7,10,15,20,30,40,60,80,100,120,140,160, and 180 min after commencement of the infusion. Group 2.…”
Section: Experimental Designmentioning
confidence: 99%
“…An infusion of ketamine was administered at a constant rate of 10 mg kg ±1 min ±1 over 5 min; serial arterial blood samples were taken before, then at 1. 5,3,5,7,10,15,20,30,40,60,80,100,120,140,160, and 180 min after commencement of the infusion. Group 2.…”
Section: Experimental Designmentioning
confidence: 99%
“…A DARS value <27.0 also remained a significant independent predictor of delirium risk in the derivation cohort (OR 5.4, 95% CI: (1.6, 21.1); p<0.014) while accounting for dosage of other anesthetic drugs that can affect EEG parameters (i.e. opioids, 26 non-depolarizing neuromuscular blockers, 27 ketamine, 28 midazolam and propofol 29 ) and the use of epidural anesthesia 30 and/or nitrous oxide 31 (Table 4). None of these other variables were significantly associated with postoperative delirium risk.…”
Section: Resultsmentioning
confidence: 93%
“…This robustness of the DARS for predicting delirium, despite varying doses of other drugs that can affect the EEG (i.e. opioids, 26,33 ketamine, 28 non-depolarizing neuromuscular blockers, 27 nitrous oxide, 31 etc), suggests that lower brain anesthetic resistance in response to volatile anesthetics is relatively greater in magnitude than the EEG changes due to these other anesthetic drug adjuncts. Further, the DARS was an independent predictor of delirium in two separate cohorts from two separate institutions, in whom delirium was assessed by two different groups of personnel (geriatricians vs trained research staff) using two different instruments (regular CAM vs CAM-ICU).…”
Section: Discussionmentioning
confidence: 99%
“…Classical examples in which a difference in concentration–effect curves was observed after different routes of administration are quinidine [ 26 ], and verapamil [ 27 , 28 ]. Meanwhile, changing the rate and route of administration and characterizing the pharmacodynamics upon the administration of different doses has become an accepted approach in the validation of PK–PD models as is illustrated for midazolam [ 29 ], alfentanil [ 30 ], and N 6 cyclopentyl-adenosine [ 31 ].…”
Section: Separating Pharmacokinetic and Pharmacodynamic Variabilitymentioning
confidence: 99%
“…In contrast for the 5-HT 1A receptor agonists buspirone, it was demonstrated that the active metabolite 1-(2-pyrimidinyl)-piperazine contributes significantly to the effect following administration of the parent drug [ 62 ]. Furthermore, for benzodiazepines and 5 HT 1A receptor agonists the role of interactive metabolites was studied by direct administration [ 63 ] [ 64 ], while for synthetic opioids and dopamine D 2 receptor antagonists, the analysis of the effect upon repeated administration enabled the characterization of acute functional tolerance development [ 30 , 61 ].…”
Section: The Impact On Pharmacodynamics Research: Towards Physiology mentioning
confidence: 99%